A safety study on intrathecal delivery of autologous mesenchymal stromal cells in rabbits directly supporting Phase I human trials. Issue 5 (21st November 2014) - Chen, Bingkun K.; Staff, Nathan P.; Knight, Andrew M.; Nesbitt, Jarred J.; Butler, Greg W.; Padley, Douglas J.; Parisi, Joseph E.; Dietz, Allan B.; Windebank, Anthony J.
<x xml:space="preserve">Abstract</x> Background There are no effective treatments that slow the progression of neurodegenerative diseases. A major challenge of treatment in neurodegenerative diseases is appropriate delivery of pharmaceuticals into the cerebrospinal fluid (CSF) of affected individuals. Mesenchymal stromal cells (MSCs—either naïve or modified) are a promising therapy in neurodegenerative diseases and may be delivered directly into the CSF where they can reside for months. In this preclinical study, we evaluated the safety of intrathecal autologous MSCs in a rabbit model. Study Design and Methods Autologous adipose‐derived MSCs (or artificial CSF) were delivered intrathecally, either with single or with repeated injections into the foramen magnum of healthy rabbits and monitored for 4 and 12 weeks, respectively. Results Rabbits tolerated injections well and no definitive MSC‐related side effects were observed apart from three rabbits that had delayed death secondary to traumatic foramen magnum puncture. Functional assessments and body weights were equivalent between groups. Gross pathology and histology did not reveal any abnormalities or tumor growth. Complete blood count data were normal and there were no differences in CSF interleukin‐6 levels in all groups tested. Conclusion Our data suggest that intrathecal delivery of autologous MSCs is safe in a rabbit model. Data from this study have supported two successful investigational new drug applications to the Food and Drug Administration, resulting in the initiation of two clinical trials using autologous MSCs in amyotrophic lateral sclerosis and multiple system atrophy.